Dietary Beliefs and Their Association with Overweight and Obesity in the Spanish Child Population - María Teresa Murillo-Llorente; Alma María Palau-Ferrè; María Ester Legidos-García; Javier Pérez-Murillo; Francisco Tomás-Aguirre; Blanca Lafuente-Sarabia; Adalberto Asins-Cubells; Miriam Martínez-Peris; Ignacio Ventura; Jorge Casaña-Mohedo; Marcelino Pérez-Bermejo (Children)
Background/Objectives: Childhood obesity is a multifactorial chronic disease that represents one of the main preventable causes of morbidity and mortality. This study analyzes how nutritional beliefs influence eating habits and the prevalence of overweight and obesity in Spanish children and adolescents. Methods: A cross-sectional study was conducted in 35 educational centers in 12 Spanish provinces, with a sample of 1131 children and adolescents aged 6 to 14 years. Anthropometric and sociodemographic data were collected, and dietary habits were assessed by means of questionnaires. Statistical analyses were used to identify associations between dietary beliefs and body mass index. Results: In total, 29.5% of participants were overweight or obese. Two groups of beliefs were identified: healthier beliefs and less healthy beliefs. Children with less healthy dietary beliefs had a significantly higher BMI (22.16 kg/m2) compared to those with healthier beliefs (17.2 kg/m2). False nutritional beliefs, influenced by advertising and the family environment, contribute to overweight and obesity. Discussion: Dietary beliefs play a crucial role in determining eating habits and, therefore, the health of children. Nutrition education and public policies that promote healthy eating habits are essential to prevent childhood obesity. It is important to involve the family, the school, and the media in these efforts. Conclusions: Despite efforts, many children continue to hold erroneous nutritional beliefs that contribute to the rise in overweight and obesity. This study highlights the importance of addressing dietary beliefs and promoting appropriate nutrition education to prevent childhood obesity. It is recommended to implement educational strategies and public policies that regulate the advertising of unhealthy foods and promote healthy eating habits.